A study on the Effect of Reinforcement Corrosion Using Ultrasonic Pulse Velocity Test - Jessica Tung Shi Jia; Ayop, Sallehuddin Shah (Recent Trends in Civil Engineering and Built Environment, 2024)
Reinforcement corrosion in steel is one of the major concrete deteriorations that may induce a reduction of the load-bearing capacity as well as incur underlying safety risks on the durability of the reinforced concrete structure Consequently, a routine inspection of structure that is cost-efficient and timesaving should be carried out to assure that the corrosion does not spread uncontrollably. Experimental work was conducted to study the sensitivity of reinforcement corrosion towards the Ultrasonic Pulse Velocity test (UPV) and to evaluate the presence of corrosion based on the Ultrasonic Pulse Velocity test. Two specimens of cross-section 150 x 165 and length 350 mm were reinforced with two 10mm bar diameters and used in this study. The impressed current test of 0.08mA/cm² would be conducted to accelerate the corrosion and Visual Inspection, Half-Cell Potential (HCP) method, and most importantly Ultrasonic Pulse Velocity (UPV) test would be performed for determining the sensitivity and presence of corrosion. The results indicated there is a possibility that the corrosion had taken place when the HCP reading turned down to a negative value. With the increase of corrosion, which was indicated by more negative values of HCL, the UPV values tended to decrease. Besides, the UPV method was effective in the early detection of corrosion through the validation of corrosion by Half-Cell Potential Method and Visual Inspection.